Kynurenine-PARP-1 Link Mediated by MicroRNA 210 May Be Dysregulated in Pulmonary Hypertension - Akgün, Alperen Emre; Yaylalı, Yalın Tolga; Seçme, Mücahit; Dodurga, Yavuz; Şenol, Hande (Anatolian journal of cardiology, 2022)
Dysregulation of microRNAs is associated with pulmonary hyperten-sion. The present study aimed to determine the alterations in microRNA and microRNA expressions and their role in signaling pathways and investigate the relationship with serum levels of apelin, kynurenine, and endocan in pulmonary hypertension. The study design was prospective and single-centered. The study included 32 consecutive treatment-naive patients with precapillary pulmonary hypertension and 55 age and sex-matched healthy controls. All subjects underwent right heart catheter-ization. mRNA expressions of hypoxia-inducible factor-1 alpha, hypoxia-inducible fac-tor-2 alpha, signal transducer and activator of transcription-3, fibroblast growth factor-2, fibroblast growth factor receptor-1, and poly-ADP-ribose polymerase-1 and microRNA expressions of miRNA-210, miRNA-130a, miRNA-424, miRNA-204, and miRNA-223 weredetermined by RT-PCR. Concentrations of kynurenine, apelin, and endocan were ana-lyzed by ELISA. mRNA expressions of hypoxia-inducible factor-2 alpha, signal transducer and activator of transcription-33, and FGF-2 were increased; miRNA-210 and miRNA-130a were increased; miRNA-223 and miRNA-204 were decreased in pulmonary hyperten-sion. Apelin and kynurenine concentrations were decreased in pulmonary hypertension. There were positive correlations: hypoxia-inducible factor-2 alpha-miRNA-424, Apelin- miRNA-424, kynurenine-miRNA-210, signal transducer and activator of transcription- 3-PVR, miRNA-210-right atrial pressure, and kynurenine-right atrial pressure. There were negative correlations: poly-ADP-ribose polymerase-1-miRNA-210 and poly-ADP-ribose polymerase-1-right atrial pressure. On multiple logistic regression analyses, miRNA-130a and Apelin were independent risk factors for PH. We report a novel relationship between the kynurenine and poly-ADP- ribose polymerase-1 signaling pathways that could be mediated by miRNA-210. We also report a connection between the Apelin and hypoxia-inducible factor-2 alpha signaling pathways that could be mediated by miRNA-424. Reduced levels of Apelin and elevated levels of miRNA-130a are associated with pulmonary hypertension. We also find that ele-vated levels of signal transducer and activator of transcription-3, miRNA-210, and kyn-urenine and reduced levels of poly-ADP-ribose polymerase-1 correlate with more severe hemodynamics.